ENSAT registry-based randomized clinical trials for adrenocortical carcinoma - Crona, Joakim; Baudin, Eric; Terzolo, Massimo; Chrisoulidou, Alexandra; Angelousi, Anna; Ronchi, Cristina L; Oliveira, Cristina Lamas; Nieveen van Dijkum, Els J M; Ceccato, Filippo; Borson-Chazot, Françoise; Reimondo, Giuseppe; Tiberi, Guido A M; et al. (European journal of endocrinology, 2021)
Adrenocortical carcinoma (ACC) is an orphan disease lacking effective systemic treatment options. The low incidence of the disease and high cost of clinical trials are major obstacles in the search for improved treatment strategies. As a novel approach, registry-based clinical trials have been introduced in clinical research, so allowing for significant cost reduction, but without compromising scientific benefit. Herein, we describe how the European Network for the Study of Adrenal Tumours (ENSAT) could transform its current registry into one fit for a clinical trial infrastructure. The rationale to perform randomized registry-based trials in ACC is outlined including an analysis of relevant limitations and challenges. We summarize a survey on this concept among ENSAT members who expressed a strong interest in the concept and rated its scientific potential as high. Legal aspects, including ethical approval of registry-based randomization were identified as potential obstacles. Finally, we describe three potential randomized registry-based clinical trials in an adjuvant setting and for advanced disease with a high potential to be executed within the framework of an advanced ENSAT registry. Thus we, therefore, provide the basis for future registry-based trials for ACC patients. This could ultimately provide proof-of-principle of how to perform more effective randomized trials for an orphan disease.